The Two Lives of Sara Baartman: Gender, “Race,” Politics and the Historiography of Mis/Representation - Lyons, Andrew P. (Anthropologica, 2018)
The story of Sara Baartman, the so-called Hottentot Venus, who was exhibited in both London and Paris at the beginning of the nineteenth century, is part of the long narrative of scientific racism. In the years preceding and succeeding her return to South Africa from the museum in Paris where her brain and genitals were stored, her story has been told and retold countless times by anti-racist white (and predominantly male) scholars, Pan-African anti-apartheid activists, many of them feminists, African-American scholars, and scholars who claim a particular ethnic status within the Rainbow Nation. There has been much controversy concerning the right to tell Baartman’s story and the images that may or may not accompany such narration. An attempt is made to explain why this is so.